Utilization of Sonic Bloom Technology as An Effort to Improve The Productivity of Pakcoy (Brassica rapa L.) Cultivation in The Vila Pasir Mas Taruna Tani Group - Putri, Dea Helmalia; Harahap, Fitra Syawal; Walida , Hilwa; Adam, Dini Hariyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The pak choy plant is a plant that has a very easy method of cultivation. The pak choy plant is also one of the vegetables that is often developed by hydroponic farmers because many people like to eat pak choy so this plant is one of the people's favorites. The aim of community service (PKM) is that the community is expected. Efforts to increase the productivity of pak choy continue to be made because this plant has quite high economic value and market interest. This service uses the lecture method, namely by conveying information and knowledge orally using power points. By using Sonic Bloom technology on Pakcoy plants, you can stimulate the opening of the stomata, thereby influencing the movement of carbon dioxide around the plant, thereby influencing the absorption of carbon dioxide around the leaves and more importantly using high frequency and organic sound waves. nutrients, which are proven to grow plants better to increase their productivity. By implementing this community service program, the Karang Taruna Tani Pasir Mas Group Partners will be able to provide knowledge in cultivating vegetables using Sonic Bloom technology. And based on this report, it can be concluded that Sonic Bloom treatment using the sound of the Al Quran can produce plant height, number of leaves, production weight and weight of basal roots and dry roots in bok choy plants because the sound is given using a high frequency. can stimulate the leaf mouth (somata) to remain open.